Analysis of Profitability, Liquidity, and Activity to Optimize Company Value with Capital Structure as an Intervening Variable in Metal and Mineral Manufacturing Companies Listed on the Indonesia Stock Exchange for the 2018 - 2023 Period - Hartomo, Bambang Widjanarko; Sukoco, Agus (LPPM of NAROTAMA UNIVERSITY, 2024)
Purpose: An increase in company value reflects the achievement of better overall financial performance, which is the hope of company owners and attractive to investors. This research aims to analyze the influence of profitability, liquidity and activity on company value with capital structure as an intervening variable in metal and mineral sub-sector manufacturing companies, which are listed on the Indonesia Stock Exchange for the period 2018 to 2023. Design/methodology/approach: This research uses a quantitative approach for 7 companies from 20 manufacturing companies in the metal and mineral sub-sector, which are listed on the Indonesia Stock Exchange. The data was processed using the SEM-PLS technique. The research data is secondary data, the company's financial reports on the official website www.idx.co.id and the company website. The variables used are Profitability (X1), Liquidity (X2), Activity (X3), Capital Structure (Z) and Company Value (Y). Findings: The research results show that profitability directly has a positive and significant influence on company value, liquidity is directly positive and not significant on company value. The activity ratio directly has a negative and insignificant effect on company value. Profitability has a negative and insignificant effect on capital structure. Liquidity has a negative and significant effect on capital structure. Activity Ratios have a positive and significant effect on capital structure. Capital structure has a positive but not significant influence on company value. Profitability and liquidity on company value through capital structure are negative and insignificant. The activity ratio's effect on firm value through capital structure is positive and not significant. The findings of this research indicate the importance of profitability in a strategy to increase company value with liquidity, activity and capital structure as supporting factors that must be managed carefully and carefully. Research limitations/implications: This research is limited to metal and mineral sub-sector manufacturing companies listed on the Indonesian Stock Exchange for the period 2018 to 2023. For generalization so that further research can be carried out on other sub-sector manufacturing companies. Practical implications: The results of this research can be used as a reference for increasing company value as a reflection of achieving better overall financial performance in manufacturing companies in the metal and mineral sub-sector.. Originality/value: The research results explain that among the variables are profitability, liquidity, activity ratio and capital structure can be optimally applied to increase company value in the metal and mineral industry.. Paper type: This paper can be categorized as research paper